2006 IEEE 4th World Conference on Photovoltaic Energy Conference 2006
DOI: 10.1109/wcpec.2006.279460
|View full text |Cite
|
Sign up to set email alerts
|

Growth of High-Quality CuGaSe2 Thin Films using Ionized Ga Precursors

Abstract: We have newly proposed a novel growth method for high quality CuGaSe2 (CGS) thin films in which ionized Ga was used as new source material. The films were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), and Raman spectroscopy. The grain size enlargement was successfully demonstrated by using ionized Ga precursors. The experiments revealed that the local heating caused by energy released from high energy Ga ions was one of possible reasons of this grain size enlargement and that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
(10 reference statements)
0
3
0
Order By: Relevance
“…It is reported that these binary compound can be removed by etching in KCN solution or rapid annealing using hydrogen and nitrogen mixture gas. [17] Resistivity šœŒ and carrier concentration š‘ š‘ of CIGS films on PI sheet with different compositions were performed by the van der Pauw technique. [18] Film thickness was measured by stylus profiler.…”
Section: -2mentioning
confidence: 99%
“…It is reported that these binary compound can be removed by etching in KCN solution or rapid annealing using hydrogen and nitrogen mixture gas. [17] Resistivity šœŒ and carrier concentration š‘ š‘ of CIGS films on PI sheet with different compositions were performed by the van der Pauw technique. [18] Film thickness was measured by stylus profiler.…”
Section: -2mentioning
confidence: 99%
“…In our previous study, we have developed an ionization Ga k-cell technique for CuGaSe 2 films deposition, and also found the crystal quality was obviously improved [6]. In this paper, the ionization Ga k-cell was applied to the growth of Cu(In,Ga)Se 2 (CIGS) films with lower (Ga/III = 0.30) and higher Ga (Ga/III = 0.70) content.…”
mentioning
confidence: 99%
“…The typical structure of ionization Ga K-cell has been described elsewhere [6]. The grid ionization voltage (V c ) and filament current (I fila ) are the key parameters for the ionization of Ga atoms.…”
mentioning
confidence: 99%